Ancient xiongnu (xiongnu) and kyrgyz. Public administration, legal norms, punishment system (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article examines public administration, legal norms and the system of punishment of the ancient Huns (Xiongnu) and Kyrgyz. Further, the state structure, legal norms, and the system of punishment among the Huns, the ancient nomads of Central Asia, are analyzed. In addition, the legal norms and punishment systems of the Kyrgyz were comprehensively studied according to Chinese chronicles, Arabographic written sources and epitaphal written monuments of the ancient Kyrgyz on the Yenisei. The state law and customary law, which was used by the majority of the people, and its evolutionary development are examined. In fact, as a product of the Khan’s legislation, the source of public law was to a certain extent opposed to the Yosun folk customs that regulated the sphere of private relations
Keywords: customary law, Xiongnu (Xiongnu), Kyrgyz, law, Tore, criminal cases, fine, yosun